Prospects of equitable and sustainable seaweed aquaculture: a case study of changing gender and socio-economic relations in Maullín, Chile - Fernandez, Gloria L. Gallardo; Avila, Marcela; Saunders, Fred; Riquelme, Ricardo; Rodriguez, Daniel; Aroca, Gesica; Gutierrez, Juan (My University, 2024)
This article examines the development of marine tenure in the Maullin River, Chile. It starts with the emergence of artisanal red algae (Gracilaria chilensis) gathering and the changes resulting from the governmental ad hoc allocation of small-scale aquaculture concessions. We aim to track this transition, its drivers, effects on the work organization, gender relations, market relations and the sustainability/equity challenges currently confronting the community. We use a feminist political ecology approach to direct our multi-method data collection strategy and to analyse the empirical material. The State by enabling local tenure for the development of marine aquaculture concessions played an influential role in Maullin community attaining de facto territorial tenure. This led to the establishment of residential aquaculture communities while facilitating the integration of women in aquaculture activities. We see both steps as positive economic and social development opportunities in Maullin. While marine tenure has provided livelihood chances, low prices caused by the producers' disadvantaged market position and the lack of supportive alliance building pose ongoing problems. We conclude that these factors are serious challenges to the sustainability of aquacultural livelihoods at Maullin River. While the case depicts aspects of women's empowerment such as their engagement in developing potential post-production innovation ideas, entrepreneurial abilities to conduct market transactions as well as their better competence in literacy, math and financial expertise, there is still a long way to reach gender equality in the male-dominated aquacultural sector.
Keywords: gender; small-scale aquaculture; coastal communities; gracilaria chilensis (pelillo); sustainability; political ecology